POE Activity Enriched with Augmented Reality: Conceptual Change on Pressure in Liquids - Pektaş, Hüseyin Miraç; Çelik, Harun; Karamustafaoğlu, Orhan (Jurnal Pendidikan Fisika Indonesia, 2024)
An experiment thought to be simple is included in various textbooks to test the accuracy of the principle that as the depth of the liquid increases, the pressure it exerts on the surface increases. The enriched prediction, observation, and explanation (POE) strategy was used by combining 3D animations with the interaction, convenience, and three-dimensional visualization of augmented reality (AR) to eliminate this misconception, which is still common today. Thus, this study aimed to perceive a conceptual change in teacher candidates regarding the pressure of liquids. The findings showed that teacher candidates made mistakes in the Prediction stage of POE. It was determined that the candidates observed the distances taken horizontally through their activities during the Observation stage, commented on how the distances changed, and perceived their mistakes. The Explanation stage of POE showed that teacher candidates became aware of the discrepancy between their predictions and observations, which prompted them to think. In this respect, it can be said that establishing the depth context in liquid pressure through the path taken by the fluid moving in the form of a horizontal launch through a small hole opened on the side surface of a cylindrical bottle provides a significant conceptual change. The conceptual change of the candidate teachers was significantly improved in a positive way, and the contradiction between their predictions and observations was eliminated by discussion